2012
DOI: 10.1249/mss.0b013e318258bcd5
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Cognitive Control during and after Walking in Preadolescent Children

Abstract: These findings suggest selective exercise-induced changes to cognitive control for aspects of inhibitory control and attention but not for working memory. Furthermore, the findings suggest that short bouts of exercise may be efficacious for maintaining cognitive performance, which may have implications for scholastic achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 30 publications
5
90
3
3
Order By: Relevance
“…Neither PA nor cognitive engagement nor a combination of these factors yielded a stronger improvement in cognitive performance than a passive sedentary control condition. This result, especially the non-existing effect on inhibition, contradicts our hypotheses and most previous research (Best, 2012;Chen et al, 2014;Drollette et al, 2012;Hillman et al, 2009;J€ ager et al, 2014;Kubesch et al, 2009;Pontifex et al, 2013).…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Neither PA nor cognitive engagement nor a combination of these factors yielded a stronger improvement in cognitive performance than a passive sedentary control condition. This result, especially the non-existing effect on inhibition, contradicts our hypotheses and most previous research (Best, 2012;Chen et al, 2014;Drollette et al, 2012;Hillman et al, 2009;J€ ager et al, 2014;Kubesch et al, 2009;Pontifex et al, 2013).…”
Section: Discussioncontrasting
confidence: 95%
“…Each task took about 10 min to complete and the order of the two tasks was counterbalanced between participants. Updating was assessed by a non-spatial n-back task (adapted from a spatial n-back task in Drollette et al, 2012). Several pictures of fruits were presented one after another on the screen.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10,23 The improvement in selective attention following a single physical activity bout in our study is somewhat lower than the improvement demonstrated in the study of Janssen et al, 23 in which 10-11 year old children completed the Sky Search test before and immediately after a 15-min moderate-intensity physical activity break. Janssen et al 23 demonstrated a decrease of 8.0% in selective attention scores, whereas we found a decrease of 4.1% (i.e.…”
Section: Discussioncontrasting
confidence: 75%
“…To counter the lower reliability of executive function measures, this study used a withinsubjects design and included pretest measures for each condition, including using them as a covariate in the model. Additionally, very recent work has suggested that select executive functions may be more sensitive to acute physical activity, such as selective attention and inhibition, rather than working memory (Drollette, Shishido, Pontifex, & Hillman, 2012).…”
mentioning
confidence: 99%